Role of Nepal Ophthalmic Society as a Professional Association - Malla, Tejsu; Sahu, Sabin (Nepalese Journal of Ophthalmology, 2025)
Introduction: Role of professional organisations is to set and promote standard, ultimately creating professional and personal excellence in supportive environment. Nepal Ophthalmic Society (NOS) plays crucial role in advancing ophthalmology in Nepal through education, research, and advocacy. Established in 1985 AD to promote professional development and enhance health care delivery, NOS has grown from handful of ophthalmologists, to 504 members and 50 associate members (2024 November 20). Objective: To assess perspectives of ophthalmologists on impact, activities, and role of NOS. To prepare framework for future to strengthen its organisation with happy members. Methodology: A cross-sectional survey was conducted among ophthalmologists in Nepal from 2024 May to 2024 July using structured questionnaire. The survey assessed their perspectives on NOS’s impact, activities, and role in advancing ophthalmology. Data were collected through online surveys, ensuring a representative sample of practising ophthalmologists across Nepal. Result: The study included 309 ophthalmologists and residents. Majority were young (60.1% aged ≤40 years) and female (54%). Most participants (49.52%) believed primary function of NOS was professional development, followed by advocacy, and public awareness (34.73%). The mean satisfaction rating for NOS’s role was 5.6 ± 1.85 out of 10. The major challenges faced by ophthalmologists in Nepal included low salary and financial difficulties (25.72%) as well as poor residency training and lack of surgical exposure (22.51%); 75.56% of respondents considered misuse of ‘Doctor” title by non-ophthalmologists a significant issue, with most suggested solutions being press releases and public awareness campaigns (63.43%), followed by notifying regulatory bodies (39.62%) Conclusion: The NOS has been significantly contributing to professional development, advocacy, and skill enhancement in Nepal. Key challenges include low salaries, inadequate surgical training, and misuse of ‘Doctor” title. Strengthening membership outreach, advocating professional rights, and addressing concerns will enhance NOS’s impact and ensure its long-term sustainability in shaping Nepal’s ophthalmology landscape.